2022
DOI: 10.11648/j.ijae.20220701.12
|View full text |Cite
|
Sign up to set email alerts
|

Economic Analysis of Potato Basic Seed Production Under Contract Farming in Kavrepalanchok, Nepal

Abstract: In Nepal, potato basic seed production under contract farming is at the initial phase. However, pre-basic seed potatoes were produced in Nepal since 1989/90, production of the basic seed has been relatively low, despite the government's lucrative subsidy on the price of pre-basic seed. There have been very limited studies on the production and economics of potato-basic seed under contract farming. This study examines the cost of production, resources use efficiency, return to scale, and various problem associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 7 publications
0
2
1
Order By: Relevance
“…In the same manner, a study of vegetable in the Parsa district of Nepal by Paudel et al (2021) found the highest share of the cost for labor (48.26%), afterward, followed by fertilizer cost (13.89%) and agrochemicals cost (12.54%). However, the contradictory to the outcome presented by Bolakhe et al (2022), who pointed out the cost of seed occupied (43.76%) and labor cost found to be (12.31%) for vegetable production.…”
Section: Cost Of Inputs Used In Vegetable Productioncontrasting
confidence: 58%
“…In the same manner, a study of vegetable in the Parsa district of Nepal by Paudel et al (2021) found the highest share of the cost for labor (48.26%), afterward, followed by fertilizer cost (13.89%) and agrochemicals cost (12.54%). However, the contradictory to the outcome presented by Bolakhe et al (2022), who pointed out the cost of seed occupied (43.76%) and labor cost found to be (12.31%) for vegetable production.…”
Section: Cost Of Inputs Used In Vegetable Productioncontrasting
confidence: 58%
“…The significant loss of stored seeds, which was primarily due to the lack of a cold storage facility, is what led to the increased cost of seeds. The seed tuber cost was the highest cost of production in the findings from Kavrepalanchok district (Bolakhe et al, 2022) and the Terai region of Nepal (Subedi et al, 2019). But in Achham, the cost of labour was highest, followed by the cost of seeds (Sapkota et al, 2019).…”
Section: Production Cost Of Potatoesmentioning
confidence: 91%
“…Seed material is one of the most crucial inputs in potato cultivation, as it constitutes approximately 30-40% of the total cost of cultivation [4,46]. Therefore, improving seed production management is highly important for both potato producers and consumers.…”
Section: Toward the Futurementioning
confidence: 99%